2017
DOI: 10.1039/c7ob00558j
|View full text |Cite
|
Sign up to set email alerts
|

Blue-light-promoted carbon–carbon double bond isomerization and its application in the syntheses of quinolines

Abstract: A blue-light-promoted carbon-carbon double bond isomerization in the absence of any photoredox catalyst is reported. It provides rapid access to a series of quinolines in good to excellent yields under simple aerobic conditions. The protocol is direct, catalyst-free and operationally convenient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…a base‐mediated aldol condensation between 2‐nitrobenzaldehyde and selected methyl ketones (see SI for full details). [18a] The corresponding aldol products were obtained in generally high yield and allowed for further elaboration of the nitro group into the desired amine species. To achieve this chemoselective reduction we opted to employ iron powder (ca.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…a base‐mediated aldol condensation between 2‐nitrobenzaldehyde and selected methyl ketones (see SI for full details). [18a] The corresponding aldol products were obtained in generally high yield and allowed for further elaboration of the nitro group into the desired amine species. To achieve this chemoselective reduction we opted to employ iron powder (ca.…”
Section: Resultsmentioning
confidence: 99%
“…in the presence of catalytic amounts of acid (HCl aq.) in hot ethanol,[18a] which provided the target compounds not only in a simple and short procedure but moreover in generally high yield as the E ‐isomer (see SI for full details). Interestingly, our studies also identified small amounts (<5 %) of 2‐acylindole species (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transformation was successfully achieved via a selective UV-light irradiation at 402 nm. More recently, Wang and Zhai disclosed a blue-light-promoted carbon-carbon double bond isomerization and its application in the syntheses of quinolines in the absence of photocatalyst [22].…”
Section: Introductionmentioning
confidence: 99%